Modest Mussorgsky, Pictures at an exhibition with Vladimir Ashkenazy - Mussorgsky, Modest Petrovich 1839-1881; Mussorgsky, Modest Petrovich 1839-1881 (Allegro Films, 1983)
A documentary about one of the best-known and the most singular musical works ever composed. Featuring two complete performances of the work by Vladimir Ashkenazy: one in its orchestral version by Leo Funtek, one of the Mussorgsky original score. Written as a tribute to a lost friend, Victor Alexandrovich Hartmann, it is a strange and moving masterpiece which has become Mussorgsky's most popular work. It is also probably the most frequently orchestrated piano piece of all time. It is nevertheless largely misunderstood, perhaps precisely because it is so widely known in other composers' arrangements, in particular the orchestration by Maurice Ravel which, in the opinion of Vladimir Ashkenazy, is very far removed from the spirit of Mussorgsky's original for the piano. He insists that it is not an entertainment piece, nor an attempt to describe or illustrate Hartmann's drawings in music. He sees it as a profoundly felt expression of Mussorgsky's view of life. Vladimir Ashkenazy is uniquely qualified to guide us to the heart of Mussorgski's unusual masterpiece. He is a Russian-born and Russian-trained musician, capable both of playing the original piano work (in recital at the Barbican Center at the end of this programme) and of conducting the orchestral version by Leo Funtek (with the Swedish Radio Orchestra), as well as anybody on the concert platform today. The important element in this film is the idea that, for all the splendour and popular success of the orchestral versions, they all lack something of the quality and power of Mussorgsky's original composition for the piano, particularly in the hands of Ashkenazy
Keywords: Suites (Piano); Suites (Orchestra), Arranged; Mussorgsky, Modest Petrovich / 1839-1881 / Kartinki s vystavki; Kartinki s vystavki (Mussorgsky, Modest Petrovich); Internet videos